PENGARUH KREDIBILITAS CELEBRITY ENDORSER TERHADAP MINAT BELI KONSUMEN - Jatmiko, M. Roby (STIE Totalwin Semarang, 2013)
The purpose of this study is to test whether the source credibility affects buying intention. The influence that endorser credibility dimensions (i.e. attractiveness, trustworthiness and expertise) have on purchase intentions of 100 young consumers has been examined. The results showed that all of the three credibility dimensions have a positive relationship with purchase intention